2005
DOI: 10.1142/s0192415x05002904
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Attitudes to Traditional Chinese Medicine Among Chinese Medical Students

Abstract: We studied the attitudes and personal experiences with traditional Chinese Medicine (TCM) use in Chinese medical students. Medical students at the Chinese University of Hong Kong were asked 13 questions according to an anonymous survey. Six hundred and eleven of 780 medical students (47% males, 52% females) returned the questionnaire; 199 (33%) of the participants used TCM at least once in the past year, and 85% had ever tried various TCM. The attitude was positive in 41%, neutral in 52% and negative in only 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…In our study, the female students held a more positive attitude toward CAM than the male students. Junior students were more positive than senior students (50.07 ± 7.642 vs 47.59 ± 9.34, p < 0.001), which is consistent with the investigation in other countries [12,25,27,28]. e lower grade students had a stronger desire to learn CAM than higher grade students (89% vs 83%, p < 0.05).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study, the female students held a more positive attitude toward CAM than the male students. Junior students were more positive than senior students (50.07 ± 7.642 vs 47.59 ± 9.34, p < 0.001), which is consistent with the investigation in other countries [12,25,27,28]. e lower grade students had a stronger desire to learn CAM than higher grade students (89% vs 83%, p < 0.05).…”
Section: Discussionsupporting
confidence: 89%
“…e proportions of students who held positive, neutral, and negative attitude toward TCM were in 52%, 41%, and 6%, respectively [11,12]. However, the abovementioned research was only conducted in one school, and the respondents were restricted to students of pharmacy and Chinese medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Medical students also believed that CAM should be studied by biomedical practitioners before integration with modern medicine could occur (21). Among students of healthcare, medical students had the least knowledge of CAM, with comparative studies of medical students versus nursing and pharmacy students showing higher levels of CAM knowledge amongst these non-medical health student groups (15,23,25,29).…”
Section: Methodsmentioning
confidence: 99%
“…There was a high preference for evidence-base as a pre-requisite to inform CAM inclusion in medical curriculum, with eighteen papers highlighting this strong preference among medical students, clinicians and faculty (10,12,13,15,19,20,23,24,(28)(29)(30)33). This preference was not absolute, with 41% of Singaporean medical students also suggested that they would accept CAM based on long-standing traditions (such as TCM), even if it had not been tested in a scientific way (15).…”
Section: Methodsmentioning
confidence: 99%
“…However, demographic factors (education, age, gender) did not predict 6 WM physician visits in a sample of immigrant Chinese elders in the US 15 . Indeed, surveys of Chinese students in Hong Kong suggest that TCM use might not be restricted to particular demographic groups within this sub-population: 85% of medical students 16 92% of nursing students 17 and 96% of pharmacy students 18 reported past TCM use. In comparison, amongst western-trained doctors in China older doctors had more positive attitudes to TCM than younger doctors 19 .…”
Section: Some Population Characteristics Have Been Associated With Usmentioning
confidence: 99%